Conflict Management in Islamic Education Institutions (Case Study at Madrasah Ibtidaiyah in Jombang) - Nurul Indana; Sulistyorini Sulistyorini; Khumairoh An Nahdliyah (STAI Terpadu Yogyakarta, 2023)
Conflict is inevitable in the world of education. The existence of conflict can have both positive and negative impacts. Handling conflicts with fast and appropriate strategies will have a positive impact on the institution. This study aims to determine the form of conflict that occurs as well as the methods and styles of handling conflicts carried out by the head of the madrasah. This research is qualitative research with the type of case study. The type of conflict that occurs in MI al Urwatul Wutsqo is the type of conflict between the head of the madrasa and the teacher, interpersonal conflict is the conflict that occurs between teachers. Conflict management between madrasah heads and teachers is carried out by deliberation and consensus, voting and inviting foundation administrators to provide solutions. Handling conflicts between teachers is carried out in a collaborative style through three stages, namely 1) the head of the madrasah identifies the cause of the conflict, 2) understands well the conflict that is happening. 3) Resolve conflicts by bringing in conflicting parties.